Guidelines for Physical Activity During Pregnancy: Comparisons From Around the World. (March 2014) - Evenson, Kelly R.; Barakat, Ruben; Brown, Wendy J.; Dargent-Molina, Patricia; Haruna, Megumi; Mikkelsen, Ellen M.; Mottola, Michelle F.; Owe, Katrine M.; Rousham, Emily K.; Yeo, SeonAe
Introduction . Women attain numerous benefits from physical activity during pregnancy. However, because of physical changes that occur during pregnancy, special precautions are also needed. This review summarizes current guidelines for physical activity among pregnant women worldwide. Methods . We searched PubMed (MedLINE) for country-specific governmental and clinical guidelines on physical activity during pregnancy through the year 2012. We cross-referenced with articles referring to guidelines, with only the most recent included. An abstraction form was used to extract key details and summarize. Results . In total, 11 guidelines were identified from 9 countries (Australia, Canada, Denmark, France, Japan, Norway, Spain, United Kingdom, United States). Most guidelines supported moderate-intensity physical activity during pregnancy (10/11) and indicated specific frequency (9/11) and duration/time (9/11) recommendations. Most guidelines provided advice on initiating an exercise program during pregnancy (10/11). Six guidelines included absolute and relative contraindications to exercise. All guidelines generally ruled-out sports with risks of falls, trauma, or collisions. Six guidelines included indications for stopping exercise during pregnancy. Conclusion . This review contrasted pregnancy-related physical activity guidelines from around the world, and can help inform new guidelines as they are created or updated and facilitate the development of a worldwide guideline.